A study on the Turkish mother's perception of a child with Down Syndrome and her social adjustment - (:unkn) unknown (My University, 1998)
Objective: This investigation is designed to examine the needs and concerns of the mothers, and the variables that influence their acceptance of their Down Syndrome (DS) children, perception, attitudes and social adjustment. Methods: Thirty-two mothers (aged 23-50 years) who graduated from primary school (16 cases), high school (11 cases) or university (5 cases) were included. The questionnaire survey that contained three parts of 72 questions was given to the mothers. Results: The initial feelings when the mothers first learned of their children's condition were regret for the child and/or themselves (78%), disbelief and shock (59%), disappointment (44%), guilt (19%) and/or anger (16%). These feelings were not related to the mothers' educational level (p > 0.05). Twenty-six (81%) of the mothers with different educational levels succeeded in accepting their child and his/her disability after they attributed the responsibility of misfortunes to 'God's will/fate' or genetic causes. The number of spouses who easily accepted their children's condition was higher than that of those who experienced difficulties in accepting (p < 0.04). Eighty-five percent of the mothers believe that Turkish people generally understand their feelings and their child's condition (p < 0.001). The primary concern of the mothers about their children is fear of the future. The majority of the mothers expect the support of the state for their disabled children's needs such as education and employment. Conclusion: This study showed similarities in the experiences of the mothers with different educational levels in many aspects such as their emotion, reactions and expectations. The first step for planning of any support is the acceptance of the child with DS at all levels; parents, professionals, government and society.
Keywords: Down syndrome; Quality of life